Knowledge Management in Botswana Sport: Current Status and Future Directions - Moustakas Louis; Işık Arda Alan (Sciendo, 2021)
In Botswana, sport is positioned as a potential driver of economic and social development. In particular, there are numerous discussions about increasing the socio-economic impact of sport and the need to professionalise Botswana sport. Knowledge Management (KM) can play a critical role in achieving this greater professionalisation and impact. Despite this importance, there have only been a small number of studies on KM in sports, and none of this literature explores the topic in sub-Saharan Africa. Against this background, the goals of our paper are two-fold. Firstly, we wish to map out the current knowledge management landscape in the Botswana sport sector. Secondly, we aim to propose concrete, evidence-based avenues to improve KM within the sector. This paper relies on findings generated through semi-structured qualitative interviews with individuals connected to Botswana sport. To allow for triangulation, these interviews are further supported by other, previous qualitative research as well as relevant academic and policy literature. The Knowledge Management framework from Sunassee and Sewry (2002) is used to analyse and structure the results. Overall, we see that KM in Botswana sport is somewhat present at the individual, organisational level, but numerous obstacles and inefficiencies exist in creating and sharing knowledge at the sectoral level. To support the growth of KM in the sector, numerous concrete recommendations are presented. In particular, we highlight a need to communicate the value of KM better and obtain the necessary buy-in.